Results of introduction of Rhodiola rosea L. in the conditions of Chernivtsy State University Botanical Garden - Romanjuk, V.V.; Galycka, L.G.; Derevenko, T.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
Introduction of Rhodiola rosea L. into culture is the most effective way of its preserving. The characteristics of morphological peculiarities of Rh. rosea in the conditions of Chernivtsy State Univercity Botanical Garden is given. The peculiarities of Rh. rosea growth processes in plain conditions of North Bukovina are elucidated. The dependence of quality officinal primary products from set in of certain development phases is definited. The conformity of accumulation of biologically active substances from plants age have been shown. The climate conditions of North Bukovina favorurable for introduction of Rh. rosea into culture.